The Impact of Cooperative Learning Models on Students’ Comprehension of Natural Events in Science Education - Andi Asrifan; Raveenthiran Vivekanantharasa; Sivaraja S; Musdalifah (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2025)
This research examines the influence of the Team Games Tournament model on student involvement and academic achievement in scientific education. A mixed-methods strategy was employed to obtain quantitative data through tests, which indicated that a substantial percentage of pupils attained high scores, reflecting a robust comprehension of the topic. Qualitative observations emphasized active engagement, cooperation, and enthusiasm among students during collaborative activities. The results indicate that the interactive characteristics of the Team Games Tournament cultivate a favorable learning atmosphere, augmenting students' enthusiasm and critical thinking abilities. The existence of pupils in lower score ranges highlights the necessity for tailored interventions to assist struggling learners. The research underscores the significance of tailored education and the establishment of inclusive learning environments to address diverse student requirements. The incorporation of collaborative learning practices in science education enhances academic performance and equips students with vital skills, like cooperation and communication, for future difficulties.